Procedures for Eliciting Time Preferences - David Freeman; Paola Manzini; Marco Mariotti; Luigi Mittone (Institute for the Study of Labor (IZA), 2016)
We study three procedures to elicit attitudes towards delayed payments: the Becker-DeGroot-Marschak procedure; the second price auction; and the multiple price list. The payment mechanisms associated with these methods are widely considered as incentive compatible, thus if preferences satisfy Procedure Invariance, which is also widely (and often implicitly) assumed, they should yield identical time preference distributions. We find instead that the monetary discount rates elicited using the Becker-DeGroot-Marschak procedure are significantly lower than those elicited with a multiple price list. We show that the behavior we observe is consistent with an existing psychological explanation of preference reversals.
Keywords: C91; D9; 330; time preferences; elicitation methods; Becker-DeGroot-Marschak procedure; auctions; multiple price list